Kedudukan Mahar dalam Sistem Perkawinan Adat Mandar - Andi Dewi Pratiwi (Alauddin Law Development Journal)
This study aims to analyze the legal position of spending money and the completeness of spending money in the Mandar customary marriage system. Arrangements regarding the existence and rights of indigenous and tribal peoples in Indonesia are contained in the 1945 Constitution. It can be seen in Article 18B paragraph (2), Article 281 paragraph (3). So that the Passorong agreement as well as the spending money agreement and the completeness of the spending money are part of the traditional rights of customarylaw which are acknowledged to exist. The spending money agreement is one of the prerequisites for a marriage in the Mandar Tribe which is a prestige that is poured in the form of a commitment or agreement between the two parties, namely the families of the prospective groom and the prospective bride. Seeing the elements of the spending money agreement and the completeness of this spending money where through a meeting to make a mutual agreement by making an agreement between the two parties, this agreementgave birth to an agreement which means the fulfillment of the contents of Article 1320 of the Civil Code concerning the legal terms of an agreement.